Covalent character of hydrogen bonds enhanced by π-electron delocalization - Grabowski, Slawomir Janusz (Array, 2009)
Summary: Interactions classified as intermolecular resonance assisted hydrogen bonds (RAHBs) are analyzed here. Hence the MP2/6-311++G(d,p) calculations for dimers of formic, acetic and pyrrole-2-carboxylic acid (PCA) were performed. The similar calculations were carried out for formamide and its fluorine derivatives’ dimers as well as the tautomeric forms of the latter species. The Quantum theory of Atoms in Molecules (QTAIM) and the decomposition of the interaction energy are applied to analyze hydrogen bonds enhanced by the π-electron delocalization. It is indicated that these interactions possess the covalent character. It is expressed by the negative values of the total electron energy density at the protonacceptor bond critical point as well as by the meaningful contribution of the delocalization interaction energy